السياسة اخلارجية االمريكية حيال ايران مرحلة ما بعد االتفاق النووي 5+1 - Shamal Husni Mustapha (QALAAI ZANIST JOURNAL, 2019)
One of the most important questions of the foreign policy of America while the administration of Donald trump, is the question of Confrontation influence and dominance of Iran in the Middle East and the question of Internal intervention countries in the area, in which directly makes negative effects over supreme strategies of America. In sure, during the last centuries there are strong conflicts between these two countries somewhat the relation between them became complex and danger especially in the Nuclear weapons question. Even in 2015, countries 5+1 with Iran could had a nuclear agreement, that’s after a lot of along international diplomacy Attempt. But after starting the administration of Donald Trump, He was progress the new strategy and the main sector was the Confrontation Iran and Withdrawal in the nuclear agreement. The hypothesis of the research is the originally of the relationship between America and Iran after the Islamic revolution in 1979, was conflicts, with the elites and authorities in Iran that’s continued during now of polity of the state. The Future Relationships between these two countries will never going to be better. that’s clear, the strategy of Obama tried to the relation became closer and better with the slow diplomacy Disturbed of Iran. But Trump trying to Disturbed of Iran in the hard diplomacy with Pressing and Economic sanctions